Synthesis and in Vitro Cytotoxicity Evaluation of Phenanthrene Linked 2,4- Thiazolidinediones as Potential Anticancer Agents - Yadav, Upasana; Vanjari, Yogesh; Laxmikeshav, Kritika; Tokala, Ramya; Niggula, Praveen K.; Kumar, Manoj; Talla, Venu; Kamal, Ahmed; Shankaraiah, Nagula (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Objective: To synthesize a series of phenanthrene-thiazolidinedione hybrids and explore their cytotoxic potential against human cancer cell lines of A-549 (lung cancer), HCT-116 and HT-29 (colon cancer), MDA MB-231 (triple-negative breast cancer), BT-474 (breast cancer) and (mouse melanoma) B16F10 cells. Methods: A new series of phenanthrene-thiazolidinedione hybrids was synthesized via Knoevenagel condensation of phenanthrene-9-carbaldehyde and N-alkylated thiazolidinediones. The cytotoxicity (IC50) of the synthesized compounds was determined by MTT assay. Apoptotic assays like (AO/EB) and DAPI staining, cell cycle analysis, JC-1 staining and Annexin V binding assay studies were performed for the most active compound (Z)- 3-(4-bromobenzyl)-5-((2,3,6,7-tetramethoxyphenanthren-9-yl)methylene)thiazolidine-2,4-dione (17b). Molecular docking, dynamics and evaluation of pharmacokinetic (ADME/T) properties were also carried out by using Schrödinger. Results and Discussion: From the series of tested compounds, 17b unveiled promising cytotoxic action with an IC50 value of 0.985±0.02μM on HCT-116 human colon cancer cells. The treatment of HCT-116 cells with 17b demonstrated distinctive apoptotic morphology like shrinkage of cells, horseshoe-shaped nuclei formation and chromatin condensation. The flow-cytometry analysis revealed the G0/G1 phase cell cycle arrest in a dosedependent fashion. The AO/EB, DAPI, DCFDA, Annexin-V and JC-1 staining studies were performed in order to determine the effect of the compound on cell viability. Computational studies were performed by using Schrödinger to determine the stability of the ligand with the DNA. Conclusion: The current study provides an insight into developing a series of phenanthrene thiazolidinedione derivatives as potential DNA interactive agents which might aid in colon cancer therapy.
Keywords: cell cycle arrest